2011
DOI: 10.1038/onc.2011.134
|View full text |Cite
|
Sign up to set email alerts
|

P73 regulates cisplatin-induced apoptosis in ovarian cancer cells via a calcium/calpain-dependent mechanism

Abstract: P73 is important in drug-induced apoptosis in some cancer cells, yet its role in the regulation of chemosensitivity in ovarian cancer (OVCA) is poorly understood. Furthermore, if and how the deregulation of p73-mediated apoptosis confers resistance to cisplatin (CDDP) treatment is unclear. Here we demonstrate that TAp73α over-expression enhanced CDDP-induced PARP cleavage and apoptosis in both chemosensitive (OV2008 and A2780s) and their resistant counterparts (C13* and A2780cp) and another chemoresistant OVCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 48 publications
5
70
0
Order By: Relevance
“…[11][12][13][14][15] It is involved in several biological processes, such as cell death, [16][17][18][19] differentiation, [20][21][22] neuronal stem cell maintenance, [23][24][25][26] the amino acid Glutamine is converted into Glutamate by a deamidation reaction catalyzed by the enzyme Glutaminase (GLS). two isoforms of this enzyme have been described, and the GLS2 isoform is regulated by the tumor suppressor gene p53.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] It is involved in several biological processes, such as cell death, [16][17][18][19] differentiation, [20][21][22] neuronal stem cell maintenance, [23][24][25][26] the amino acid Glutamine is converted into Glutamate by a deamidation reaction catalyzed by the enzyme Glutaminase (GLS). two isoforms of this enzyme have been described, and the GLS2 isoform is regulated by the tumor suppressor gene p53.…”
Section: Introductionmentioning
confidence: 99%
“…[81][82][83][84] Both p63 and p73 isoforms have been linked to resistance to cisplatinum in ovarian as well as triple-negative breast cancer cells lines. 85,86 Data from human studies are few, but one study found high expression of the p73-dominant negative isoforms (DNp73 and DN'p73) to be associated with platinum resistance in ovarian cancers harbouring TP53 mutations. 87 MDM2 AND MDM4 Although MDM2 and MDM4 execute their oncogenic effects by overexpression, the importance of each protein and lack of redundancy are illustrated by the fact that MDM2 and MDMX (the mouse homologue of MDM4) deletion in mice cause embryonic lethality, the former at the blastula stage and the latter 7-11 days into the gestation period.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%
“…Calpain activation is Ca 2ϩ -dependent, and CDDP increases intracellular Ca 2ϩ levels in chemosensitive OV2008 cells but not in its resistant variant (C13*) (40). Because calpain content is the same in both chemosensitive and resistant OVCA cells (Fig.…”
Section: Cddp Effectmentioning
confidence: 99%